The complete chloroplast genome of the Juglans regia (Juglandales: Julandaceae). (4th May 2017) - Peng, Shaobing; Yang, Guiyan; Liu, Chaobin; Yu, Zhongdong; Zhai, Meizhi
Abstract: The complete nucleotide sequence of Juglans regia chloroplast genome (cpDNA) was carried out using Illumina Hiseq 2500. The genome is 160 537 bp in length, and the overall base composition of H-strand is 31.59% for A, 18.35% for C, 17.76% for G and 32.30% for T. Similar to the other higher plants, cpDNA have a large single copy (LSC) region of 90 059 bp and a small single copy(SSC) of 18 412 bp, is separated by a pair of inverted repeats (IRa and IRb) of 26 033 bp. There are 113 genes in the cpDNA, including 80 protein-coding genes, 4 ribosomal RNA genes (4 rRNA species), 36 transfer RNA genes (19 tRNA species). To further investigate the evolution status of J. regia in the level of chloroplast genome, tree constructed using MEGA 6.0 with NJ and ML methord demonstrated J. regia was clustered in Fagales, which was identical with APG III.